Effect Of The Tourism Sector On Economic Growth In Solo Raya, Central Java Province - Katno Katno; Heru Subiyantoro (Al-Makki Publisher, 2024)
This study expects to examine the impact of vacationer visits, lodging inhabitance rates, and unfamiliar direct speculation (FDI) on the monetary development of Solo Raya from 2013 to 2022. Financial development implies changes in the economy of a district. The exploration uses auxiliary information from 7 locale/urban communities, specifically Surakarta City, Boyolali Rule, Sukoharjo Regime, Karanganyar Rule, Wonogiri Regime, Sragen Rule, and Klaten Regime, handled through board information investigation utilizing the Decent Impact Model (FEM) technique. The consequences of this study show that, to some extent, the quantity of vacationers has a positive and huge relationship with monetary development, lodging inhabitance rates likewise have a positive and critical relationship with financial development, and FDI has a positive and critical relationship with monetary development. Simultaneously, the number of tourist visits, hotel occupancy rates, and FDI collectively influence Economic Growth in the Java Island Province from 2013 to 2022.